Perception of College Service Quality, Social Support, and Self Regulation as Predictor of College Student Subjective Well Being (RETRACTED) - Putri, Asri Mutiara; Lutfianawati, Dewi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Subjective well-being is an indicator of mental health that plays an essential role in college students because it significantly predicts academic achievement and dropout rates. This study aimed to determine the effect of perceptions on the quality of higher education services, social support, and self-regulation on college students' subjective well-being. The sample in this study was 325 college students from various universities in Indonesia. The data in this study were obtained through the College Student Subjective Well-Being Questionnaire, the Higher Education Performance Scale, the Multidimensional Scale of Perceived Social Support, and the Self Regulation Questionnaire to measure variables in this study. The collected data were then analyzed using multiple linear regression. This study showed that student perceptions of college service quality, social support, and self-regulation significantly influence college students' subjective well-being. Student perceptions of the college service quality were the main predictor of college students' subjective well-being. The implication of this research was that to improve the subjective well-being of college students, a comprehensive approach is needed that includes quality services from universities, social support, and good self-regulation skills in students.